Monitoring adherence to drug treatment by using change in cholesterol concentration: secondary analysis of trial data. - Bell, K; Kirby, A; Hayen, A; Irwig, L; Glasziou, P (2011)
OBJECTIVE: To estimate the accuracy of monitoring cholesterol concentration for detecting non-adherence to lipid lowering treatment. DESIGN: Secondary analysis of data on cholesterol concentration in the LIPID (long term intervention with pravastatin in ischaemic disease) study by using three measures of non-adherence: discontinuation of treatment, allocation to placebo arm, less than 80% of pills taken. SETTING: Randomised placebo controlled trial in Australia and New Zealand. PARTICIPANTS: 9014 patients with previous coronary heart disease. INTERVENTIONS: Pravastatin 40 mg or placebo daily. MAIN OUTCOME MEASURES: Sensitivity, specificity, area under the receiver operating characteristics (ROC) curve, post-test probability. RESULTS: Monitoring of cholesterol concentration had modest ability for detecting complete non-adherence. One year after the start of treatment, half (1957/3937) of the non-adherent patients and 6% (253/3944) of adherent patients had a rise in concentration of low density lipoprotein cholesterol. Accuracy was reasonable (area under the curve 0.89). Cholesterol monitoring, however, had weak ability for detecting partial non-adherence. One year after the start of treatment, 16% (34/213) of partially adherent and 4% (155/3585) of fully adherent patients had a rise in concentration of low density lipoprotein cholesterol. Accuracy was poor (area under the curve 0.65). For typical pre-test probabilities of non-adherence ranging from low (25%) to high (75%), the post-test probabilities indicate continuing uncertainty after lipid testing. A patient with no change in low density lipoprotein cholesterol concentration has a post-test probability of being completely non-adherent of between 67% and 95% and a post-test probability of being partially non-adherent of between 48% and 89%. A patient with a decrease in concentration of 1.0 mmol/L has a post-test probability of being completely non-adherent of between 7% and 40% and a post-test probability of being partially non-adherent of between 21% and 71%. CONCLUSIONS: Monitoring concentration of low density lipoprotein (or total) cholesterol has modest ability to detect complete non-adherence or non-persistence with pravastatin treatment and weak ability to detect partial non-adherence. Results of monitoring should be considered as no more than an adjunct to careful discussion with patients about adherence.